Archéologie d'un paysage Les étangs de Saint-Blaise (Bouches-du-Rhône) - Trément, Frédéric (Documents d'archéologie française, 1999)
This work presents the findings of research conducted from 1988 to 1993 near the étang de Berre. On the basis of systematic surveying, soundings and the excavation of a Gallo - Roman establishment,F Trément situates the major sites of Saint-Blaise and the Fossæ Marianæ in a globally and dynamically perceived space. Using earth and life sciences (geomorphology, sedimentology, palynology...). and with recourse to texts and iconography, the archaeologist broadens his focus, to encompass the landscape in its entirety. This microregion is characterised by numerous closed depressions, which explain the high population density during the Neolithic, the Iron Age and in Antiquity, and constitute sedimentary records of the evolution of the surroundings. The author seeks to understand how the successive waterside communities adapted to this shifting and harsh environment, how they appropriated the space and set about exploiting it, more or less consciously, leaving their mark, more or less enduring.